Sustainable Nutrition in a Changing World - Biesalski, Hans Konrad; Drewnowski, Adam; Dwyer, Johanna T.; Strain, JJ; Weber, Peter; Eggersdorfer, Manfred (Springer International Publishing : Imprint: Springer, 2017)
This book is the first of its kind to tackle in detail the nutritional requirements of the industrialized, so-called developed world. It discusses the link between socio-economic status and food security, focusing especially on the relationship between income and food security in different age groups. The authors calculate the actual levels of essential micronutrients delivered by current dietary patterns, identifying important shortfalls in the provision of key micronutrients, and elucidate the public health consequences of nutrition insecurity. Finally, the authors discuss future approaches for ensuring nutrition security on the basis of three pillars: access, availability and nutritional value. The approaches advocated in this ground-breaking publication will allow all people, irrespective of age and social status, to have access to a safe and nutritious diet. Key stakeholders such as legislators, government, academia and industry, as well as consumers themselves, all have important roles to play in making this a reality.